Technology-mediated research competencies: An analysis of university faculty at the University of Granma - Antúnez Sánchez, Armando Guillermo (2025)
Technology-mediated research competencies enhance the generation of innovative knowledge among teachers, which favors their adaptation to current educational challenges. This research aims to characterize the current state of technology-mediated research competencies among university professors at the University of Granma. A quantitative, exploratory-descriptive approach was used, with a non-experimental design. The sample consisted of 54 professors. The results highlight that 70.4% of the professors show Good and High levels of research competency development, and 29.6% show average or low ratings. The study concludes that 70.4% of the professors possess solid research skills, but 57.4% lack digital research competencies, with only 16.7% at an optimal level. The distribution (48.1% average, 24.1% low) reflects institutional policy demands for training in technological tools for research.